Repercussions of neonatal good practices from the children's assistance profile (Research, Society and Development, 2020)
The objective of this study was to identify the repercussions of good neonatal practices from the birth care profile. A quantitative, descriptive, documentary and retrospective study conducted with the verification of 1062 electronic medical records of pregnant women who were attended at the time in delivery in a low risk maternity, from June 2018 to May 2019. For the analysis were performed relative frequencies and absolute values also a Chi-square test was applied. Significant differences were considered, with results of p